Planning and implementing ecological corridors in the southeast Atlantic Forest: Challenges and opportunities - Ribeiro, João Vitor Mariano [UNESP] (2024)
Designing ecological corridors studies are much more common than studies that evaluate the effectiveness and practicality of implementation. Thus, this study aimed to identify and discuss factors that can influence the implementation of ecological corridors designed from a multicriteria analysis. For this purpose, the ecological corridor implementation efforts of a Non-Governmental Organization (NGO) in an Atlantic Forest region were evaluated. The following information about the restoration projects was collected from the NGO database: georeferenced restoration polygons, restoration technique, project size, motivation, and land use tenure characteristics of the restoration site. Restoration polygons were spatially referenced to the planned corridor areas and classified according to land use and land cover, slope, distance to roads and occurrence in Permanent Preservation Areas. The NGO implemented 455.0 hectares of restoration, with only 10.7% within proposed corridors. NGO projects were concentrated on ecological restoration, which presents significant differences between ecological corridors. In practice, the implementation of restoration areas was primarily guided by the local characteristics of the landscape, project’s constraints and the will and interest of rural landowners in restoring their properties. This differs from its planning, in which social and economic aspects were not considered and only the environmental variables were taken into.